Morphology of silicon/silicon-oxide nanowires grown from nickel-coated silicon wafers - Li, Feng Ji (2015)
Silicon (Si) nanowires are important building blocks in the devices of photonics, quantum-dots, optoelectronics and energy. So far, however, the morphology is yet well studied. In this work, Si/Si-oxide nanowires were grown through thermal annealing of nickel (Ni) coated Si wafers. Side-by-side biaxial, smooth or sinusoidal triple-concentric, fishbone-profiled, Ni-nanosphere entrapped nanowires, and the transitional morphologies were observed co-existing with the most abundant coaxial ones. The relation between the nanowires and the seeding particles is carefully explored via transmission electron microscopy and selected area electron diffraction pattern. In conjunction with the scrutiny of the existing mechanisms, it is found that the morphology of the nanowires is controlled by the diameter, vibration, phase distribution, and the eutectic precipitation of the seeding Ni–Si–O droplets. A detailed growth mechanism is proposed.